2019
DOI: 10.1002/pi.5876
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of poly(acrylic acid)–Fe3+/gelatin/poly(vinyl alcohol) triple‐network supramolecular hydrogels with high toughness, high strength and self‐healing properties

Abstract: Hydrogels with good mechanical and self‐healing properties are of great importance for various applications. Poly(acrylic acid)–Fe3+/gelatin/poly(vinyl alcohol) (PAA‐Fe3+/Gelatin/PVA) triple‐network supramolecular hydrogels were synthesized by a simple one‐pot method of copolymerization, cooling and freezing/thawing. The PAA‐Fe3+/Gelatin/PVA triple‐network hydrogels exhibit superior toughness, strength and recovery capacity compared to single‐ and double‐network hydrogels. The mechanical properties of the synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The tensile curves clearly showed that with the increasing self-healing time, the recovery degree of mechanical properties became higher, and the sample could be recovered almost entirely after 48 h of contact at RT (Figure 4C), which could be a synergic effect of metal migration and coordination, hydrogen bonding, and electrostatic interactions between the two polymer networks. 38 In addition, Figure 4D showed the healing of electrical conductivity after putting two separated pieces of gels together in which the conductivity could be rapidly recovered within seconds. Both the mechanical and electrical self-healing performance could satisfy the demand of fabricating self-healing stretchable devices, in which the healing could be accelerated with external heat activation according to previous literatures.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The tensile curves clearly showed that with the increasing self-healing time, the recovery degree of mechanical properties became higher, and the sample could be recovered almost entirely after 48 h of contact at RT (Figure 4C), which could be a synergic effect of metal migration and coordination, hydrogen bonding, and electrostatic interactions between the two polymer networks. 38 In addition, Figure 4D showed the healing of electrical conductivity after putting two separated pieces of gels together in which the conductivity could be rapidly recovered within seconds. Both the mechanical and electrical self-healing performance could satisfy the demand of fabricating self-healing stretchable devices, in which the healing could be accelerated with external heat activation according to previous literatures.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Both the mechanical and electrical self-healing performance could satisfy the demand of fabricating self-healing stretchable devices, in which the healing could be accelerated with external heat activation according to previous literatures. 7,38,41 Regarding the degradation performance, unlike single-network gelatin organohydrogel 7 or Fe 3+ -cross-linked PAA hydrogel 24 that could turn into the liquid state in DI water after a few days, the GEL/PAA-GL organohydrogels were found to be stable in water for at least 1 week owing to the stronger interactions between gelatin and PAA networks. However, by elevating the temperature or adding other reagents such as glycerol or sodium citrate to dissociate the metal ions from carboxyl groups, the degradation time of GEL/PAA-GL could be remarkably reduced.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…At the same time, gelatin molecules were entrapped in the network of PMAA and, after cooling down to 4°C, formed physical cross‐links due to triple helices formation. [ 32 ] Water entrapped in the structure of hydrogels acted as a porogen, contributing to the high porosity of the hydrogels. The resulting materials were constituted from highly porous interpenetrating networks of covalently cross‐linked PMAA and physically cross‐linked gelatin.…”
Section: Resultsmentioning
confidence: 99%
“…Tensile tests of the composite hydrogels were conducted with reference to the ASTM D638 standard, with slight modification [45]. Uniaxial tensile tests on rectangular hydrogel strips (50 mm × 10 mm × 1.0 mm) were performed on an Instron 5567 universal testing machine at a crosshead speed of 10 mm/min.…”
Section: Physical Properties Of Sipc Hydrogelsmentioning
confidence: 99%